2011
DOI: 10.1111/j.1365-2958.2010.07516.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa flagellum confers resistance to pulmonary surfactant protein‐A by impacting the production of exoproteases through quorum‐sensing

Abstract: SummarySurfactant protein-A (SP-A) is an important antimicrobial protein that opsonizes and permeabilizes membranes of microbial pathogens in mammalian lungs. Previously, we have shown that Pseudomonas aeruginosa flagellum-deficient mutants are preferentially cleared in the lungs of wild-type mice by SP-Amediated membrane permeabilization, and not by opsonization. In this study, we report a flagellummediated mechanism of P. aeruginosa resistance to SP-A. We discovered that flagellum-deficient (DfliC) bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 72 publications
5
48
0
Order By: Relevance
“…Also, there are reports of elastase inactivating secretory immunoglobulin A, immunoglobulin G and opsonin C3 [31], [48]–[50]. Most recently, we have confirmed that P. aeruginosa LasB is able to degrade lysozyme in vitro [22], [51].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Also, there are reports of elastase inactivating secretory immunoglobulin A, immunoglobulin G and opsonin C3 [31], [48]–[50]. Most recently, we have confirmed that P. aeruginosa LasB is able to degrade lysozyme in vitro [22], [51].…”
Section: Introductionsupporting
confidence: 75%
“…Also, SP-A activates phagocytic cells and upregulates the expression of host cell-surface receptors involved in microbial recognition [8], [17][21]. Most recently, we and others have reported that SP-A also directly kills microbes in a macrophage-independent manner by increasing the permeability of microbial membranes [22][27]. However, the mechanism by which SP-A permeabilizes microbial membranes and its relative importance in the lung defense is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…4B). Prolonged exposure abolished the difference of phagocytic efficiency between 1244 and ⌬tfpO strains, most probably due to the production of exoproteases that degraded SP-A, as we had previously reported (28,32). These observations were confirmed by in vivo phagocytosis assays, which showed that ⌬tfpO bacteria were 4.5-fold more susceptible to SP-A-mediated phagocytosis than was strain 1244 (Fig.…”
Section: Glycosylation Of Tfp With O-ag Is Important For Resistance Tsupporting
confidence: 81%
“…As discussed above, SP-A mediates its antimicrobial effects by enhancing microbial clearance through membrane permeabilization and opsonization (22,24,(28)(29)(30)(31)(32). To further examine whether O-glycosylation of P. aeruginosa Tfp with O-ag increases the resistance to SP-A-mediated membrane permeability, we measured the amounts of leaked thiol containing proteins from 1244 versus ⌬tfpO mutant after exposure to hSP-A.…”
Section: Glycosylation Of Tfp With O-ag Is Important For Resistance Tmentioning
confidence: 99%
See 1 more Smart Citation